ELECTRONIC INTERACTION OF BUSINESS ENTITIES DURING GLOBAL CHALLENGES - DANICH, VITALIY; TATAR, MARYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Global challenges are stepping up the transition to electronic forms of interaction. With their help business processes, communicative, managerial functions are realized. The existing schemes of electronic interaction are analized in the article, the systematization of their advantages and disadvantages is done and the factors influencing the development of electronic interaction in Ukraine are offered. The factors and mechanisms of transformation of traditional forms of interaction are determined and the possibility and expediency of transition to electronic forms are analyzed, the difference of which is cooperation using publicly available information systems and computer networks. The basic concepts related to interaction via the Internet are described, the indicators that determine the development of e-commerce are identified, their dynamics in Ukraine and in the world are analyzed. The following methods were used in the research process: analysis, synthesis, generalization, induction, analogy, comparison, system approach. The analysis of statistical data made possible to note the low level of GDP per capita in Ukraine compared to other European countries. The percentage of e-shoppers and the percentage of e-GDP, i.e. GDP sold through e-commerce, is also low in Ukraine. Although it should be noted that Ukraine is among the ten countries with the largest number of online users, therefore, the country has great potential for doing e-business. During such global challenge as pandemic, there was a significant intensification of electronic forms of interaction in response to the socio-behavioral constraints caused by the pandemic. The results of the research showed that e-interaction has both undeniable advantages and certain threats to eliminate which further action of both private and public sectors should be directed.